Essential Oil Volatile Fingerprint Differentiates Croatian cv. Oblica from Other Olea europaea L. Cultivars - Marijana Popović; Maja Jukić Špika; Maja Veršić Bratinčević; Tonka Ninčević; Ana Matešković; Marija Mandušić; Jakša Rošin; Marija Nazlić; Valerija Dunkić; Elda Vitanović (Molecules, 2021)
Olive leaves are a highly available by-product from table olive and olive oil production. They are nowadays strongly valuable for their major bioactive compounds and their beneficial effects. To determine the differences between two Croatian domestic (Lastovka, Oblica) and two introduced (Leccino, Frantoio) cultivars, physical and chemical analysis of olive leaves were performed: surface area, color variability, total phenolic amounts, and essential oil volatile profiles were analyzed at three harvest periods. All cultivars greatly differed in surface area, with cv. Lastovka being the smallest. Color variability resulted in an overall decrease in darkness and amounts of green and yellow that could be attributed to a decrease in photosynthetic demand and chlorophyll content. The highest amount of total phenolic content occurred in the summer months, followed by a reduction until October. Essential oils volatiles were determined by GC-MS and showed great diversity not only amongst cultivars but also between harvest periods, with overall 45 compounds identified. Principal component analysis distinguished domestic cultivar Oblica from the other observed cultivars, mainly due to its essential oil volatile fingerprint. Compounds that differentiated cv. Oblica were aldehydes ((E,Z)-2,4-heptadienal, (E,E)-2,4-heptadienal, decanal), ketones ((E)-β-damascone, dihydrodehydro-β-ionone), sesquiterpenes (cyclosativene, α-copaene, α-muurolene) and saturated hydrocarbons (tetradecane, hexadecane). Essential oil volatile fingerprint attributed the highest to the biodiversity of domestic cv. Oblica through all three harvest periods.